Clinical Case of a Patient with Acute Tricuspid Valve Infective Endocarditis and A Multiplex Approach to Evaluation of The Complication Risk - E. O. Kotova; Zh. D. Kobalava; A. S. Pisaryuk; A. V. Lokhonina; A. Y. Moiseeva; E. A. Domonova; J. I. Babukhina; P. V. Kakhktsyan; Т. Kh. Fatkhudinov (Архивъ внутренней медицины, 2025)
Infective endocarditis (IE) is characterized by the difficulty of diagnosis, treatment and risk assessment of an unfavorable prognosis. Currently there are no approved scales and calculators for the risk of complications and death that help the practitioner make decisions, especially in patients with isolated right-sided IE. For right-sided IE, the timing of successful surgical treatment remains uncertain. Previously developed risk calculators (Italian Rizzi calculator and French Hubert) are poorly validated in a wide population of patients with IE, especially for right-sided IE. One of the required parameters of calculators is the determination of etiological affiliation. However, with negative results of microbiological studies reaching 56-83 %, this parameter becomes uninformative. Moreover, existing risk assessment tools do not take into account the activity of the disease (including laboratory activity), which intuitively is an important guideline for every doctor in decision-making. At the moment, there is a great need for the introduction of molecular biological methods to improve the quality of etiological diagnosis and in-depth study of possible biomarkers from simple (neutrophil/lymphocytic, platelet/lymphocytic and systemic immuno-inflammatory index) to more complex (neutrophil extracellular traps, cytokine profile). We present a clinical case of a young patient with acute tricuspid valve IE with giant vegetation (28 mm), complicated by severe valvular insufficiency without signs of heart failure, recurrent embolic syndrome in the pulmonary artery system with the formation of pulmonary hypertension, determining indications for cardiac surgical treatment. The etiological affiliation of IE to Staphylococcus aureus was established only by PCR. The urgent timing of intervention was determined based on an increase in new markers — neutrophil/lymphocytic index ≥20.0, systemic immuno-inflammatory index ≥2314.0 and neutrophil extracellular traps ≥14.2, indicating an extremely high risk of death. A fundamental pathohistological study of the tissue material revealed a low content of intact CD86+ proinflammatory macrophages, probably associated with their excessive destruction and uncontrolled release of copious amounts of proinflammatory cytokines, which led to rapid and severe damage to the tricuspid valve. Thus, modern management of patients with IE should be multiplex using current methods of etiological and imaging diagnostics, and aimed at early detection of patients at adverse risk for a timely differentiated approach to conservative or cardiac surgical treatment tactics.